2008
DOI: 10.2174/092986608786071157
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Nickel-Binding Peptides in a Human Hepidermoid Cancer Cell Line by Ni-NTA Affinity Chromatography and Mass Spectrometry

Abstract: To elucidate whether eukaryotic elongation factor 1A (eEF-1A) in a human hepidermoid cancer cell line (H1355) belonged to the family of the Ni-interacting protein, we analyzed the sequence of peptides obtained by on-Ni-NTA-agarose tryptic digestion of proteins from H1355 cell extract. LC/MS analysis showed the presence of several peptides mainly from abundant cellular proteins corresponding to eEF-1A, tubulin and actin. The results indicated that F-actin strongly binds to Ni-NTA-agarose whereas the other prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…A recent example of eEF1A1 involvement in apoptosis suggests that this protein mediates lipotoxic cell death through a mechanism independent from changes in the rates of protein synthesis. Since eEF1A1 plays an important role in remodelling microtubules and filamentous actin [56,69,70] and because the cytoskeleton undergoes dramatic changes during apoptosis and cell death, eEF1A1 may mediate cytoskeletal changes required to execute cell death programs in response to lipotoxic conditions [71].…”
Section: Eukaryotic Elongation Factor 1amentioning
confidence: 99%
“…A recent example of eEF1A1 involvement in apoptosis suggests that this protein mediates lipotoxic cell death through a mechanism independent from changes in the rates of protein synthesis. Since eEF1A1 plays an important role in remodelling microtubules and filamentous actin [56,69,70] and because the cytoskeleton undergoes dramatic changes during apoptosis and cell death, eEF1A1 may mediate cytoskeletal changes required to execute cell death programs in response to lipotoxic conditions [71].…”
Section: Eukaryotic Elongation Factor 1amentioning
confidence: 99%
“…Several studies have been carried out in which different molecules have been identified to interact with eEF1A, either involving the entire protein or just localized regions within specific domains, some reviewed in section 1.3.3.1. Thus, it has been shown that (i) F-actin interacts with domains I and III of Dictyostelium EF1α (Liu, et al, 1996) and domain II of human eEF1A from an epidermoid cancer cell line (Lamberti, et al, 2008); (ii) activation-induced deaminase (AID) binds to Domain III of eEF1A leading to cytoplasmic retention (Hälser, Rada and Neuberger, 2012); (iii) SH3 domain-containing adaptor protein SORBS2, involved in the assembly of signaling complexes, interacts with domain II of eEF1A1 near the membrane (Lamberti, et al, 2011); and (iv) SH2 and SH3 domains of diverse signaling molecules, such as Crk, Fgr, Fyn, Grb2, RasGAP, Shc and Shp2, possess different abilities to bind to phosphotyrosine-containing sites in domain I of both eEF1A1 and eEF1A2 (Panasyuk, et al, 2008). Further studies directed at characterizing eEF1A complexes and the PTMs involved are required to clarify, at the molecular level, the plethora of events in which this elongation factor is involved.…”
Section: Resultsmentioning
confidence: 99%
“…As actin cytoskeleton shown significant perturbations in cancer cells), eEF1A2 may contribute to the oncogenic transformation of cells (Stevenson, Veltman and Machesky, 2012. Furthermore, it has been shown that F-actin interacts with domains I and III of Dictyostelium EF1α (Liu, et al, 1996) and domain II of human eEF1A from an epidermoid cancer cell line (Lamberti, et al, 2008).…”
Section: Macromolecular Partners Of Eef1a and Other Non-canonical Funmentioning
confidence: 99%